INTITUTIONAL ARRENGGEMENTS IN LOCAL GOVERMENT SERANG CITY THROUGHT MAPPING DISTRICT PETENTIAL BASED ON LOCAL WISDOM PRINCIPLES - Karsa, Pipih Ludia; Mu’in, Fatkhul (Legal Standing : Jurnal Ilmu Hukum, 2020)
Structuring through mapping can be done at the district level which has characteristicsthat can be the same and also different, but the structuring process needs to be based onlocal wisdom in order to maintain the cultural identity and values that grow anddevelop in the midst of society. For this reason, structuring will be correlated withpotential mapping, to support regional administration in the city of Serang bymaintaining the values of local wisdom in each district. This is intended to correlate thepotential with the authority possessed by other institutions (offices) so that it will havean impact on determining the competency of the apparatus human resources in thedistrict appropriately. Based on data from the Serang City BPS in 2019, the subdistricts in Serang City, if viewed from the potential, area, population, agriculture,industry, sports and accommodation / hotel services have the same and differentpotentials. Taktakan Subdistrict has the most extensive area, namely 57.98, but for thepopulation of Serang District the highest, which is 228,563. For the agricultural sectorand the industrial sector, all sub-districts have it, while for Hotels / AccommodationServices, only the district of Cipocok Jaya and the District of Serang have this potential.As for sports facilities, the district of Cipocok Jaya and Walantaka do not have it. Onthis basis, the Regional Government of Serang City can develop, synchronize andharmonize the potential of sub-districts with the projected institutional arrangement.